Pengaruh Rasio Efisiensi dan Rasio Efektifitas PAD Terhadap Belanja Modal Pada Kabupaten/Kota di Jawa Barat - Rohyana, Cahyat; Dentisa Ramadhanti, Defitria (Universitas Logistik dan Bisnis Internasional, 2024)
APBD in the form of capital expenditure allocation requires good management in order to obtain effective and efficient results. Therefore, good financial performance is needed, which is measured using financial analysis tools in the form of ratios. The ratios used in the analysis of government financial performance are efficiency ratios and PAD effectiveness ratios. This research was conducted with the aim of knowing the effect of the efficiency ratio and the effectiveness ratio of PAD on the allocation of capital expenditure in districts/cities in West Java. This study uses a quantitative research type where the data used is secondary data in the form of financial reports by taking the 2018-2022 budget realization report. The samples used in this study amounted to 42 samples. The analytical tools used in this study are Data Normality Test, Product Moment Correlation Analysis, Multiple Correlation, Multiple Regression Analysis, Partial Test (t test) and Simultaneous Test (f test), Coefficient of Determination. The results of the study partially show that there is no effect of the efficiency ratio on capital expenditure in regencies/cities in West Java. Partially there is no effect of the effectiveness ratio on capital expenditure in districts/cities in West Java. The results of the study simultaneously show that there is no effect of the efficiency and effectiveness ratio of PAD on capital expenditure in regencies/cities in West Java.